Evaluating the effectiveness of mindfulness-based sexual therapy for women with sexual dysfunction: A systematic literature review - Eka, Grace; Tondok, Marselius Sampe (University of Muhammadiyah Malang, 2024)
This study aimed to explore and synthesize the effectiveness of mindfulness-based therapy in addressing sexual dysfunction that adversely impacts the quality of women sexual relationships with the partners. Systematic Literature Review (SLR) methodology was used based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. In this study, a systematic literature search was conducted on integrated databases, namely SagePub, Science Direct, Springer, and PubMed, for articles published between 2014 and 2023. The search terms used were